Mortality in severe serious adverse events following heterologous and homologous prime-boost vaccination strategies for SARS-CoV-2: A retrospective cohort study - Min Cheol Song; Jongmok Ha; Suyeon Park; Hyunwook Kang; Taeeun Kyung; Namoh Kim; Dong Kyu Kim; Kihoon Bae; Kwang Jun Lee; Euiho Lee; Jin Myoung Seok; Jinyoung Youn (PLoS ONE, 2025)
The COVID-19 pandemic underscored the urgent need for widespread vaccination to achieve herd immunity and mitigate severe outcomes. To address vaccine supply constraints, heterologous prime-boost strategies were adopted in Korea and other countries. Although studies have explored the effectiveness of heterologous prime-boost SARS-CoV-2 vaccination, comprehensive research on its adverse events (AEs), particularly severe serious AEs (SAEs), remains lacking. As an observational study, this study aims to compare severe SAEs across vaccination strategies and examine factors, including heterologous vaccination, associated with 42-day mortality among patients with severe SAEs, without implying causality. Our retrospective cohort study involved 358 cases of severe SAEs following prime-boost SARS-CoV-2 vaccination in Gyeonggi Province, South Korea, from February 26, 2021, to March 15, 2022. In patients with severe SAEs, the heterologous vaccination was associated with a higher risk of mortality than the homologous viral vector vaccination. Vaccinations performed at vaccination centers were associated with a lower risk of mortality. Furthermore, among patients with severe SAEs, the heterologous group exhibited a higher rate of respiratory diseases and genitourinary diseases compared to the homologous viral vector group. Moreover, the rate of deaths from genitourinary diseases among patients with severe SAEs was significantly higher in the heterologous group compared to the homologous viral vector group. We believe that our study, while limited to associations and not establishing causality, provides critical insights that could inform decision-making in scenarios where heterologous vaccination is necessitated by vaccine shortages or other constraints, particularly in managing severe SAEs and improving patient outcomes.